(untitled) (Nonconventional Technologies Review, 2025)
Laser beam cutting of metallic workpieces is a frequently used process nowadays, due to the possibilities of cutting according to predetermined contours and the relatively small size of the slit width resulting from cutting. The heights of surface asperities resulting from cutting depend on the values ​​of some input factors in the cutting process. To obtain more information on the influence of some input factors in the laser beam cutting process on the surface roughness achieved by laser beam cutting, experiments were carried out in which the values ​​of the laser beam power, cutting speed, gas pressure, and pulse frequency, respectively, were changed. The experimental results were mathematically processed, being established empirical mathematical models capable of highlighting the direction and intensity of the influence exerted by the input factors considered on the value of the roughness parameter Ra, for the two distinct areas of the surface resulting from laser beam cutting. If in the case of the area of ​​penetration of the laser beam into the test sample, the factor with the greatest influence is the power of the laser beam, in the case of the surface through which the beam exits the test sample, the greatest influence is exerted by the frequency of the laser pulses.